Platelet transfusions in adult ICU patients with thrombocytopenia - Anthon, Carl Thomas (2024)
Funding Information: This study was funded by the Research Council of Rigshospitalet, the Ehrenreich's Foundation and the Dagmar Marshalls Foundation. None of the funders had any influence on the design, conduct or reporting of the study. Funding Information: The Department of Intensive Care at Rigshospitalet (CTA, AP, MHM, LR) has received funding for other research projects from Sygeforsikringen \u2018danmark\u2019, and the Novo Nordisk Foundation. FP has received honoraria for consulting and lectures from Gilead and an institutional grant from Alexion Pharma. AP has received honorarium from Novartis for participation in an advisory board. EA has received research grants from MSD Avenir and Alexion and honoraria for lectures from Alexion, Sanofi and Pfizer. AVDL has received honoraria from Sanofi for participation in an advisory board. PC has received consulting fees from Sanofi, Gilead, Alexion and Janssen and honoraria for lectures from Merck Sharp & Dohme, Gilead, Alexion and Pfizer. PP has received consulting fees from Sanofi and Gilead and honoraria from Merck Sharp & Dohme, Gilead, Mundipharma and Pfizer for academic and educational work. EC received fees for lectures and conference talks and had travel and accommodation expenses related to attending scientific meetings covered by Gilead, Shionogi B.V. and Sanofi\u2010Genzyme. ARH has received honoraria from Pfizer for lectures. MHB has received consulting fees from AM\u2010pharma and Inotrem. CL has received consulting fees from Gilead. MS has received honoraria for lectures and consulting from CSL Behring, Alexion AstraZeneca Rare Disease and Takeda. KS has received consulting fees from Paion. None of these had any relation to the current work. Publisher Copyright: © 2024 The Author(s). Acta Anaesthesiologica Scandinavica published by John Wiley & Sons Ltd on behalf of Acta Anaesthesiologica Scandinavica Foundation.